Look together: using gaze for assisting co-located collaborative search. (February 2017) - Zhang, Yanxia; Pfeuffer, Ken; Chong, Ming Ki; Alexander, Jason; Bulling, Andreas; Gellersen, Hans
Abstract Gaze information provides indication of users focus which complements remote collaboration tasks, as distant users can see their partner's focus. In this paper, we apply gaze for co-located collaboration, where users' gaze locations are presented on the same display, to help collaboration between partners. We integrated various types of gaze indicators on the user interface of a collaborative search system, and we conducted two user studies to understand how gaze enhances coordination and communication between co-located users. Our results show that gaze indeed enhances co-located collaboration, but with a trade-off between visibility of gaze indicators and user distraction. Users acknowledged that seeing gaze indicators eases communication, because it let them be aware of their partner's interests and attention. However, users can be reluctant to share their gaze information due to trust and privacy, as gaze potentially divulges their interests.